Road Infrastructure In Europe And Central Asia : Does Network Quality Affect Trade ? - Shepherd, Benjamin 1993- (The World Bank, 2007)
The authors present a new database of minimum distance road routes connecting 138 cities in 27 countries across Europe and Central Asia. They use it to show that improved road network quality is robustly associated with higher intraregional trade flows. Gravity model simulations suggest that an ambitious but feasible road upgrade could increase trade by 50 percent over baseline, exceeding the expected gains from tariff reductions or trade facilitation programs of comparable scope. Cross-country spillovers due to overland transit are important: total intraregional trade could be increased by 30 percent by upgrading roads in just three countries-Albania, Hungary, and Romania